Berbagai Faktor Risiko Retinopati Diabetik pada Penderita Diabetes Melitus Tipe 2 - Nafia, Nisa Khoirun; Nugroho, Trilaksana; Wildan, Arief; Julianti, Hari Peni; Purnomo, Hery Djagat (Medica Hospitalia : Journal of Clinical Medicine, 2021)
BACKGROUND: More than 75% of people with type 2 DM will anguish diabetic retinopathy 20 years after being diagnosed. However, the current changing of people’s lifestyle contributes to the tendency in type 2 DM that diagnosed at a younger age. This causes diabetic retinopathy can be occurred earlier and blindness will occur more quickly. It is important to prevent diabetic retinopathy by controlling some associated factors. OBJECTIVE: To investigate associated factors of diabetic retinopathy in people with type 2 DM. METHOD: Analytic observational study with cross-sectional design. Subjects were determined by purposive sampling. The subjects were interviewed using a questionnaire meanwhile, funduscopic examination is aimed to assess diabetic retinopathy and followed by deep interview. This study also used the subject’s medical record to complete the required data. The results were analyzed by using statistic software. RESULT: From 43 subjects, there wes no significant relation among age (p=0.965), gender (p=0.437), level of knowledge (p=0.640), accessibility (p=1.000), economic level (p=0.680), duration of DM (p=0.477), history of hypertension (p=0.708), and history of dyslipidemia (p=0.244) with diabetic retinopathy in people with type 2 DM. However, there was significant relation among controlling blood glucose (p=0.014) with diabetic retinopathy in people with type 2 DM. Uncontrolled blood glucose was 13 times more affected in diabetic retinopathy than controlled blood glucose (OR 13.417, 95% CI:1.474-122.117). CONCLUSION: There was a significant relation between controlling blood glucose and diabetic retinopathy in people with type 2 DM. Controlling blood glucose is the most dominant risk factor among the other factors in this study. Keywords: diabetic retinopathy; risk factor; type 2 diabetes mellitus